Determinants for the Adoption of Digitalization by Manufacturing SMEs in India: An Empirical Study - Arora, Amit Kumar; Rathi, Priya (Prabandhan: Indian Journal of Management, 2019)
The study attempted to determine the factors/determinants for the adoption of digitalization in SMEs. The study categorized various determinants into internal and external factors. To test the hypotheses, 52 sample units were studied. The results of logistic regression and chi-square test indicated that diversification, profitability, level of competition, managerial factors, and technological factors were significant for the adoption of digitalization. On the other hand, size of the firm and government initiatives were found to be the non-significant factors. Lack of support from the top management and lack of experts were found to be the major challenges for the adoption of digitalization for the firms who had not adopted digitalization.